Rethinking social impacts of tourism research: A new research agenda - Deery, Margaret (Pergamon, 2012)
Understanding the social impacts of tourism on communities is extremely important for government at all levels so that action can be taken to reduce the likelihood of a community backlash against tourists and tourism development. Given that the residents of many tourism destinations are a fundamental part of the tourism ‘product’, resident attitudes and behaviour have a sizable impact on the success or otherwise of a destination. Research on the social impacts of tourism on communities is substantial and ongoing and while advances have been made in the area, the research has not addressed some of the deep seated issues faced by tourist destinations. This paper provides a critique of the social impact of tourism literature, highlighting the inadequacies in the research that has been conducted to date, which then leads to the development of a new conceptual framework. The paper traces the key developments in social impact research and argues that the predominance of quantitative methods potentially limits our ability to gain a more in-depth understanding of the impacts and how they influence both the host community and tourists. The paper finds that the quantitative focus from previous social impact research has led to a narrow understanding of the issues surrounding social impacts and proposes a new research agenda based on ‘layers’ of social impact understanding through the use of ethnography or phenomenology. The paper concludes with recommendations to progress social impact research beyond simply describing the issues towards explanations of why they occur by suggesting that social impact research examine, in greater depth, the values and intrinsic characteristics of the host residents.